Uji Performa Penggerak Perahu Dengan Tipe Twin Menggunakan Propeller 2 Blade - Hasdiansah Hasdiansah (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Indonesia, as an archipelagic country, requiresefficient sea transportation systems, particularly forsmall to medium-sized fishing vessels. One innovationdeveloped to support this need is the twin propulsionsystem driven by a single engine. This study aims toevaluate the performance of a 2-blade propeller in atwin screw configuration, focusing on thrust, speed,efficiency, and vessel stability. The experimentalmethod was conducted through direct testing in awater tank using a 22 HP four-stroke gasoline engine,which transmitted power to two propeller shafts via achain and sprocket mechanism. The results show thatthrust increases with engine speed. At 2300 RPM, theaverage thrust obtained was 39.24 N, while at 4600RPM, it significantly increased to 78.48 N. Thesefindings confirm a linear relationship between RPMincrement and thrust production. Overall, the twinpropulsion system with a 2-blade propellerdemonstrated good performance, stability, andresponsiveness to engine speed variations. This studyis expected to serve as a reference for the developmentof propulsion systems for fishing boats and smallvessels that are more efficient and well-suited to theconditions of Indonesia’s archipelagic waters,particularly in the Bangka Belitung region.